New approaches to understanding income differences and current account imbalances - Ahmed, S (2013)
This thesis employs two new approaches to explain some of the important debates in two key economic fields: labour market economics and macroeconomic studies related to current account imbalances. Chapter 1, Chapter 2 and Chapter 3 begin a new strand of research by introducing the normal inverse Gaussian (NIG) distribution to describe unobserved heterogeneity in the labour market. The NIG distribution can be represented as a normal variance-mean mixture with the inverse Gaussian (IG) distribution as the mixing distribution. A 0.01% subsample of the 1980 US Census, comprising all men between 18 and 65 who are in the labour force, as well as a comparable sample from Ghana, is used to show that the NIG distribution provides a better fit of the log earnings function than the normal distribution. The prediction of right skewness of the log earnings distribution arising from the log normal skill Roy selection model is rejected in favour of left skewness. The thesis then extends the model to describe the distribution of log earnings conditioned on education. The same two datasets (US males and Ghanaian males) are used for the empirical analysis. We find that, once the unobserved heterogeneity is accounted for, the return to education is almost flat for lower levels of education in Ghana, and then increases for education levels greater than ten years. One of the key differences between the two datasets is that skewness and unobserved heterogeneity is a function of education for Ghana but not for the US. The NIG framework is found to be a useful tool to model this heterogeneity. Chapter 4 uses a model that allows for a rich structure of age effects similar to those predicted by the life cycle theories to argue that the demographic shifts are partly responsible for the sustained rise in the US current account deficit and the rapid increase in China's current account surplus in the last decade. However, demographics do not have an impact on the long run equilibrium or level of current accounts. Rather, they are important determinants of the short run adjustment of current accounts to their equilibrium levels. In the next twenty years, the demographic shifts are likely to push towards further current account positive adjustments in China and current account negative adjustments in the US. Developing the infrastructure, financial markets, policy tools and regulatory settings to be able to cope with the excess capital flow remains an urgent task.